Applying foresight analysis in West and Central Africa: Capacity needs assessment from a regional engagement process - Neely, Constance; Segnon, Alcade C.; Lamien, Niéyidouba; Nkoum, Marie Nicole Taha; Chesterman, Sabrina; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Identifying transformative adaptation pathways requires mainstreaming foresight analysis in both research and development planning for climate change adaptation. As a regional institution coordinating agricultural research in West and Central Africa, CORAF aims to provide leadership on strategic foresight planning in the region beyond individual projects, as emphasized in its 2018-2027 Strategic Plan. Based on the capacity needs assessment workshop, a training of trainers of the Community of Practice of Expert Foresight Facilitators will be carried out. Workshop participants identified substantive topics for which to apply foresight analysis in the region. Inclusion of gender and youth social groups in foresight analysis is a key priority focus. This includes the use of gender disaggregated quantitative and qualitative data in the situational analysis. The West and Central Africa region will benefit from a network of existing foresight initiatives, curricula development and certification efforts to support the Community of Practice.